Revisiting Argentine Spanish intonation: Córdoba and San Luis - Laura Colantoni (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
Pretonic lengthening has been reported as the most salient characteristic of Córdoba Spanish (Lang-Rigal 2014; Lenardón 2017). If the relative duration of the pretonic to the tonic is a cue to stress in Spanish (Ortega & Prieto 2011; Hualde 2015), it is worth exploring what the cues are in a variety in which pretonic syllables are longer than tonic ones. I analyze the production of oxytones, bi- and trisyllabic paroxytones and proparoxytones by six speakers from Córdoba and three from the neighbouring province of San Luis. An analysis of relative duration and intensity, as well as pitch accent types, revealed that pretonic lengthening was more prominent in and near the capital of Córdoba than in the rest of the province but was also attested in San Luis. Consistent with previous studies (Requena et al. 2013; Lang-Rigal 2014), participants from Córdoba showed a tendency to align the f0 peak within the stressed syllable but varied in the alignment of the peak depending on the type of word and the location. Overall results support the existence of a geographical continuum in the use of relative duration of tonic, pretonic and posttonic syllables (Vidal de Battini 1964) and reveal the need of more systematic explorations of the correlate of stress in different word types and across Argentine varieties.